Uma análise sobre créditos e os controles do Banco Central no Brasil entre 2007 e 2015 - Kluth, Fabian (Universidade Federal de São Carlos, 2015)
In considering the evolution of credit and rising inflationary pressure observed in Brazil between 2007 and 2015 this research investigates how the Central Bank of Brazil, given its goal of inflation targeting, acted in providing reserves to support the observed credit growth in recent years. The econometric method used for analysis consisted of applying Granger causality tests using data from the Central Bank of Brazil. We conclude that the amount of money were defined by demand and had no impact on the determination of the nominal product. The central bank, in turn, provided the necessary reserves in accordance to the volume of deposits. Together, these results provide support to the notion of endogenous money supply in the period.
An analysis over credit and central bank controls in Brazil bctwcen 2007 and20 15
Keywords: Crédito; Banco Central; Oferta monetária endógena; Credit; Banks and banking, Central; Endogenous Money Supply; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIA MONETARIA E FISCAL::INSTITUICOES MONETARIAS E FINANCEIRAS DO BRASIL